An inertial method for the solution of M-tuple split common fixed point problems involving strict quasi-Gf-pseudocontractive mappings - Jenber, Dagnachew; Zegeye, Habtu; Haile Takele, Mollalgn; Regassa Tufa, Abebe (Fixed point theory and algorithms for sciences and engineering, 2025)
This work presents an inertial method to estimate solutions to the m-tuple split common fixed point problems for strict quasi- G f -pseudocontractive mappings in (m+1) Banach spaces. Our approach can also be used to solve the extended split equality fixed point problem. Applications to the solution of extended split equality issues, such as Extended Split Equality Equilibrium Problem, Extended Split Equality Inclusion Problem, Minimization of Tikhonov Functionals in Banach Spaces and Extended Split Equality Feasibility Problem are demonstrated in the setting of real Banach spaces. To illustrate our conclusions, we end with a numerical example.